Fifty Years of Endurance: Dementia, the Abandonment of Memory, and the Possibility of Archive for a Life-long Violence Victim - Ohri , Naoko (Research Developments in Arts and Social Studies Vol. 4, 2022)
In the current epoch, history and literature interact through the medium of narratives. Historians are starting to document diverse accounts of events, having reworked the practice of research exclusively based on written records for authenticity[1]. With a greater diversity in narrative styles than ever, literature has developed to function as a means of interpreting and communicating experiences and incidents[2]. Especially considering the emergence of the archive from the history field and the increase of literary production to report catastrophic experiences, the trend of rapprochement between history and literature cannot go unheeded. Appreciating the interdisciplinary development of research in the humanities, this study aims to reclaim a neglected memory and acknowledge it as worth recording. It is expected that the current findings shall contribute to enrich the literature with subject matter on the boundaries where history, utterance, memory, and representation blur into one another. Through an indirect approach using an oral history interview[3], the author salvaged the memory of a patient with dementia who was also a survivor of kidnapping, house arrest, and domestic violence. Theoretically, the analysis relies on the literary critic Cathy Caruth [4] who applies the concept of trauma to research in the humanities, thereby finding alternative ways of explaining things at the intersection of memories and records; telling and listening; psychoanalysis, sociology, history, and literature (see also Caruth [5]). As observed by several clinicians, the victims of violence may resort to pathological loss of memory to cope with their psychological wound [6]. This study envisions the potential of the archive as a replacement of such a type of memory loss. [1] Although under radical criticism in the making of feminist scholarship since the 1980s, the authenticity of scientific research was questioned more thoroughly in the post-colonial review of history in the 1990s. Since then, alternative methods of the pursuit of knowledge have been sought outside of European tradition. For instance, see Linda Tuhiwai Smith’s Decolonizing Methodologies [1]. [2] The growing popularity of the genre of memoirs since the 2000s seemingly indicates the current of rapprochement between history and literature. Theresa Hak Kyung Cha’s [2] Dictée and Rahna Reiko Rizzuto’s [3] Hiroshima in the Morning are fine examples of that form of literary work. [3] Oral history is one of alternative methods invented in the feminist and post-colonial modification of historical research. For details of the significance of the methodology, see Reconstructing Women’s Wartime Lives by Penny Summerfield [7], specifically the “Preface and Acknowledgements.”